Strengthening Muamalah Maliyah's Literacy Understanding of Online Transactions in Indonesia - Ahmad Supriyadi; Arqhan Ravaşdeh (JOURNAL OF ISLAMIC ECONOMICS AND BUSSINES ETHICS, 2024)
This research aims to test and analyze the understanding of students majoring in Commerce Management at the ALKS study program in implementing online buying and selling schemes from an Islamic perspective, namely by using the Muamalah Maaliyaah contract. The population in this study was 278 people from each generation of the ALKS study program, a sample of at least 10 people was taken and then the sample size became 100 people. This research uses a quantitative approach. The data collection technique used was by distributing questionnaires and interviews. The model used is a simple linear regression model with statistical analysis tests used are the classical assumption test, T-test, validity, and reliability tests. The research results show that from a simple regression test, the results of the t-test variable for the variable Understanding the Muamalah Maaliyaah Agreement show t_count of 15.024 > t_tabel of 1.98472 and a Sig value of 0.000 < 0.05. These results show that "There is a significant relationship between the influence of Understanding the Muamalah Maaliyah Agreement (X) on the decision to carry out online transactions (Y)". It can be concluded that there is a very large influence of ALKS study program students' muamalah literacy on the decision to carry out online transactions.